A review of Malaysian experience in tissue engineering research and development: an online database study using Scopus - Ahmad Radzi, Muhammad Aa'zamuddin; Mohd. Azharuddin, Nur Syamimi; Hashi, Abdurezak Abdulahi; Azhim, Azran; Sha'ban, Munirah (IIUM Press, 2019)
Tissue engineering (TE) research serves to overcome the major obstacles in organ transplantation. This paper summarizes the progress of TE in Malaysia. The online database of Elsevier’s SCOPUS was accessed. Publications related to TE from 1960 till 2017 were scrutinized. The results show an increasing trend in tissue engineering research and development in Malaysia. The search result identified and examined 264 original article publications. It is hoped that the outcomes of this study could serve as a point of reference for researchers on the status of TE research and development in Malaysia. The findings of this study could assist TE researchers in Malaysia to identify the strengths, weaknesses, opportunities and obstacles towards further enhancement in their activities. Consolidating, realigning and re-strategizing those initiatives should also be seen within the context of nurturing potential and budding researchers in TE.